2012
DOI: 10.1007/8904_2012_136
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Brazilian Patients with Gaucher Disease and Fabry Disease

Abstract: Summary Objective: To evaluate QoL in a sample of Brazilian patients with Gaucher (GD) and Fabry (FD) disease using the SF-36 survey.Method: Observational cross-sectional study. The SF-36 survey was administered to cognitively able patients 12 years or older, who were seen in the Medical Genetics Service of Hospital de Clínicas de Porto Alegre, Brazil.Results: Thirty-five patients were included in the study (GD ¼ 21, FD ¼ 14), mean age was 29.8 AE 14. Discussion and Conclusion: Although limited because of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 20 publications
3
17
1
2
Order By: Relevance
“…Although, in our study it was not possible to establish a relation between the use of ERT and the magnitude of treatment response, Oliveira reported that patients older than 12 years with GD receiving ERT had a clinically significantly better QoL than patients not receiving ERT (Oliveira et al. ), so that, like in other publications, we found a positive response to ERT that was associated to an significant improvement in QoL.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Although, in our study it was not possible to establish a relation between the use of ERT and the magnitude of treatment response, Oliveira reported that patients older than 12 years with GD receiving ERT had a clinically significantly better QoL than patients not receiving ERT (Oliveira et al. ), so that, like in other publications, we found a positive response to ERT that was associated to an significant improvement in QoL.…”
Section: Discussioncontrasting
confidence: 45%
“…(); Oliveira et al. () described the effect of enzymatic replacement therapy (ERT) on the QoL of adult patients with GD measured with SF‐36 score that is useful in patients older than 16 years of age. No studies in the literature have evaluated QoL in children with GD1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of psychological and HRQoL functioning among patients with GD1 have primarily focused on adult patients (e.g., Damiano, Pastores, & Ware, ; Elstein et al, ; Giraldo et al, ; Giraldo et al, ; Hayes, Grinzald, Duffey, & Elsas, ; Masek et al, ; Oliveira et al, ; Weinreb et al, ). Adults with GD1 experience poorer health‐related quality of life (HRQoL) in the areas of physical health, level of pain, occupational functioning, and social life compared to healthy counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…No patients in this study presented with neurological impairment, parkinsonism, cognitive decline or major depression. However, we did not detect changes in the scores on the quality of life questionnaires because the time frame of this study spanned only a few months, and it is well established that ERT improves the health-related quality of life of GD patients following several years of treatment (Hayes et al, 1998;Masek et al, 1999;Oliveira et al, 2013).…”
Section: Discussionmentioning
confidence: 90%